2001
DOI: 10.1016/s1010-7940(01)00778-3
|View full text |Cite
|
Sign up to set email alerts
|

Vasoreactivity of arterial grafts in the patient with diabetes mellitus: investigations on internal thoracic artery and radial artery conduits

Abstract: Although RA rings of patients with a long duration of diabetes have decreased maximum contraction forces, their relative vasoconstriction after norepinephrine, endothelium-dependent relaxation and smooth muscle relaxation was similar to non-diabetic patients. We thus conclude that the RA is an adequate arterial conduit in the patient with diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
11
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
6
11
0
2
Order By: Relevance
“…Our findings showed normal vasomotor properties of the LITA grafts in diabetic patients and concurred with the data of Wendler et al (19), who recently showed preserved vasoreactivity of arterial conduits (internal thoracic and radial arteries) in diabetic patients who underwent myocardial revascularization. Therefore, arterial grafts of diabetic patients appear to maintain their biological integrity, even in the presence of poorly compensated glucose metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings showed normal vasomotor properties of the LITA grafts in diabetic patients and concurred with the data of Wendler et al (19), who recently showed preserved vasoreactivity of arterial conduits (internal thoracic and radial arteries) in diabetic patients who underwent myocardial revascularization. Therefore, arterial grafts of diabetic patients appear to maintain their biological integrity, even in the presence of poorly compensated glucose metabolism.…”
Section: Discussionsupporting
confidence: 93%
“…Increased superoxide production (31,32) and peroxynitrite formation (30) were suggested to explain the NO deficiency. Endothelial dysfunction was found in isolated human diabetic small (3,33,34) and large (32,35,36) arteries, but the data were not consistent (37,38). Rarely have human studies considered perturbations in the underlying cellular mechanisms of abnormal vasomotion in diabetes (32).…”
mentioning
confidence: 98%
“…5) In contrast, several groups suggested that vascular hyperreactivity, caused by hyperglycemia, is mediated by changes in the expression of signaling molecules in vascular smooth muscle cells. 6,7) Therefore, mechanisms other than endothelial dysfunction may also participate in the vascular hyperreactivity. The saphenous vein (SV) has been commonly used as a conduit for CABG because of its ready availability and suppleness.…”
mentioning
confidence: 99%